THE INFLUENCE OF MARKETING MIX ON DECISION OF BANK LEADERS IN SELECTING PERUM JAMINAN KREDIT INDONESIA MAKASSAR BRANCH AS A CREDIT GUARANTEE INSTITUTION - syamsul bahri; Abdul Rahman Kadir; Muhammad Sobarsyah (Scientium Management Review, 2023)
The study aims to analyze the influence of marketing blends consisting of product, price, promotion, location, employee, physical evidence and process on the bank director's decision to determine Perum Jamkrindo Makassar Branch as the underwriter agency, and to investigate the most dominant process blend variable in the decision of the bank director to select Perum Jamkrindo Makassar Branch as the underwriter agency. The method used in the study in quantitative – descriptive. The population consists of 35 bank directors that constitute a full sample. The data were analyzed by multiple linear regressions supported by the SPSS 16.00. The study indicates that marketing blends consisting of product, price, promotion, location, employee, physical evidence and process variables simultaneously have a positive influence on the director's decision to select Perum Jamkrindo Makassar Branch as the underwriter agency. It is reflected in the statistical F Test or simultaneous significance test (SPSS 16.00). The free variables have a significant influence under unhealthy possibility of less than 5% (P, 0.05). Partially, the T – Test indicates the location variable is the most dominant free variable that affects the bank director's decision to select Perum Jamkrindo Makassar Branch as the underwriter agency.